2010
DOI: 10.1002/app.32875
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effective process parameters influencing styrene and acrylonitrile grafting onto seeded polybutadiene latex

Abstract: A series of experiments were designed and conducted to determine the significance of process parameters in the grafting of styrene and acrylonitrile onto polybutadiene seeds in a semicontinuous emulsion copolymerization system. The significances of the parameters were obtained by comparing the variance ratios, or F values, with F-distributions. The significance level of each test (a-value) was obtained by variance analysis. The important process parameters in industrial polymerization processes are usually mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An inverse relationship between CTA amount and tensile strength is discerned, both at the lower and higher levels of the three fixed factors (reaction temperature and time and %DPNR). This phenomenon occurs because the addition of CTA amount raises the probability of reactions between free radical species and CTA, leading to reactions that prematurely terminate polymer chain length and reducing the grafting and polymerization rates, as well as polymer molecular weight, but not altering the number of grafting sites 18, 20, 25, 45. Consequently, the grafting amount, which is the weight of the graft copolymer, is lower due to a shorter grafted chain length, and this results in poor interfacial adhesion between polymer and rubber phases 45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse relationship between CTA amount and tensile strength is discerned, both at the lower and higher levels of the three fixed factors (reaction temperature and time and %DPNR). This phenomenon occurs because the addition of CTA amount raises the probability of reactions between free radical species and CTA, leading to reactions that prematurely terminate polymer chain length and reducing the grafting and polymerization rates, as well as polymer molecular weight, but not altering the number of grafting sites 18, 20, 25, 45. Consequently, the grafting amount, which is the weight of the graft copolymer, is lower due to a shorter grafted chain length, and this results in poor interfacial adhesion between polymer and rubber phases 45…”
Section: Resultsmentioning
confidence: 99%
“…Literature data indicated that the amount of graft copolymer and its composition can be controlled by polymerization conditions—e.g., reaction time and temperature, amount of chain transfer agent (CTA), type of natural rubber latex (deproteinized or fresh natural rubber latex) 20, 22–27. This implies a correlation between the polymerization conditions and the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylonitrile–butadiene–styrene terpolymer (ABS) is the largest-volume engineering thermoplastic resin which exhibits high impact resistance, sufficient thermal stability, excellent processability, and good mechanical strength. The emulsion grafting copolymerization of styrene (St) and acrylonitrile (AN) in the presence of polybutadiene (PB) seed latex particles is still the most important route in preparing high-impact ABS resin. , Although such a graft copolymerization process has been industrialized for several decades and extensive researches in terms of the effects of various process parameters and relevant structural features have been done to attain a good balance of elastomeric and thermoplastic properties that exhibit excellent toughness, good elongation at break, and excellent processability, only little work has been devoted so far to the modeling and simulation of the emulsion copolymerization despite its industrial importance. The graft copolymerization of St and AN in the presence of PB starts from a homogeneous system, and becomes heterogeneous soon after the beginning of the process, because great differences exist in the physical characteristics such as solubility parameter and polarity between poly­(styrene- co -acrylonitrile)­(SAN) and PB. The phase separation of ABS latex particles obtained by this method shows a two-phase composite with a sea–island structure, in which small spherical SAN domains (islands) are randomly dispersed in the continuous PB matrix (sea), as shown in Figure a .…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the seeded emulsion copolymerization of St and AN have been conducted to date by many researchers mostly in the presence of PB seed latex from the viewpoint of the production of ABS resin. However, these studies aimed only to clarify the effect of process parameters, such as initiator type and concentration, the weight ratios of PB seed, St, and AN initially charged, chain-transfer agent, and reaction temperature on the morphology and mechanical properties of ABS resins produced. Recently, several researchers have shown their interest in the experimental investigations on the microemulsion copolymerization of St and AN because this polymerization system can readily produce nono-size polymer particles.…”
Section: Introductionmentioning
confidence: 99%